STUDY ON THE VERTEBRAL COLUMN OF THE LARGE TOOTH FLOUNDER, PSEUDORHOMBUS ARSIUS (HAMILTON, 1822) COLLECTED FROM OMAN SEA - Jawad, Laith A. (Vietnam Journal of Marine Science and Technology, 2014)
Based on morphometry, the vertebral column of Pseudorhombus arsius may be divided into four morphologically distinct regions. The biometrical study of the length, height and width of the successive vertebrae constituting the vertebral column of Pseudorhombus arsius allows characteristic vertebral profiles to be drawn. The differences in length of vertebrae present in different regions of the vertebral column cause regionalization in this structure. These morphological descriptive parameters express a morphotype which seems to have a functional link with the anguilliform mode of swimming of the large tooth flounder.